Effect of hydroxypropylmethyl cellulose (HPMC) coating on flavour, moisture and oil content in chicken nugget - Lai, Weng Heng; Mohd Yusof Maskat, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was carried out to determine the effects of hydroxy propyl methyl cellulose (HPMC) on the flavour compounds (eugenol and limonene), moisture and oil content in chicken nuggets during frying. Chicken nugget added with 500 ppm eugenol and limonene were coated with HPMC solution (0, 0.75 and 1.5%) and then with a commercial coating (ADABI, Malaysia). Chicken nuggets were fried at 180oC for 4 min. Quantity of eugenol and limonene in the substrate (chicken meat) and coating were measured alongwith the moisture and oil content. The results showed that 0.75 and 1.5% HPMC were not able to retain either eugenol or limonene in both substrate and coating portion of the nuggets when compared to control except for eugenol in the substrate portion when using 1.5% HPMC. Application of HPMC also resulted in reduced moisture loss and oil absorption. The reduced moisture loss and oil absorption in the coating and substrate of the chicken nuggets showed that HPMC was able to form a barrier that restricted the migration of moisture from the nuggets and absorption of oil into the nuggets. However, only the 1.5% HPMC barrier formed was able to reduce the loss of eugenol in the nugget substrate. Both 0.75 and 1.5% HPMC was not able to significantly reduce the loss of limonene during frying.